Bioactive phytochemicals and pharmacological facets of Entada species in Asia: a review = Kandungan fitokimia bioaktif dan fakta farmakologi spesis Entada di Asia: satu ulasan - Salim, Khairil Syazwan; Harun, Aiza; Abdul Aziz, Noorshilawati; Daud, Shaari; Mat So'ad, Siti Zaiton (Malysian Analytical Sciences Society, 2024)
The genus Entada, belonging to the family Fabaceae or Leguminosae, is distributed throughout the tropical and subtropical regions of South America, Australia, Asia, and Africa. Entada plants exhibit a wide range of pharmacological and biological properties, and in recent decades, their active metabolites have garnered significant interest due to their proven beneficial effects in ethnomedicinal applications and biochemical studies. However, our work only focuses exclusively on reviewing the Entada species native to and dispersed throughout the Asian continent. A total of nine species of Entada are known to be native to Asia. To the best of our knowledge, only three species of Entada (Entada rheedii, Entada spiralis, and Entada phaseoloides) have been studied extensively in Asia. The genus is recognized for its remedial properties, including anticancer, antibacterial, enzyme inhibitory, antifungal, antiulcerogenic, antiprotozoal, antioxidant, and antiproliferative activities. This underscores the relevance of the Entada genus as a rich source of compounds with significant therapeutic potential.